2007
DOI: 10.1111/j.1540-8175.2007.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Ultrasound Measurement of Longitudinal, Circumferential, and Radial Strain Using 2‐Dimensional Strain Imaging in Normal Adults

Abstract: Current noninvasive techniques used to evaluate left ventricular systolic function are limited by dependence on the angle of insonation (tissue Doppler imaging/TDI) or limited by availability (MRI tagging). We utilized 2-dimensional speckle strain (epsilon) imaging (1) to establish normal values for all three epsilon vectors; (2) to compare circumferential epsilon values with circumferential shortening (midwall fractional shortening (FS(mw)); (3) to examine the relationship between left ventricular epsilon and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
108
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 157 publications
(134 citation statements)
references
References 46 publications
20
108
0
6
Order By: Relevance
“…The anterior apical and anterior midventricular regions showed the highest circumferential peak strain values. The lowest circumferential peak strain values obtained with SENC were seen at the inferior apical and midventricular regions, which is in line with others who have measured myocardial strain using either MR tagging or echocardiographic strain imaging (15,16,23). However, there are groups who observed, contrary to our findings, that the highest strain values can be obtained by MR tagging in the posterior region of the LV (2,22).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The anterior apical and anterior midventricular regions showed the highest circumferential peak strain values. The lowest circumferential peak strain values obtained with SENC were seen at the inferior apical and midventricular regions, which is in line with others who have measured myocardial strain using either MR tagging or echocardiographic strain imaging (15,16,23). However, there are groups who observed, contrary to our findings, that the highest strain values can be obtained by MR tagging in the posterior region of the LV (2,22).…”
Section: Discussionsupporting
confidence: 88%
“…Comparing our strain values obtained by SENC to strain values generated with other imaging modalities in previous published studies, such as echocardiographic speckle tracking and tissue Doppler (15,20,21), we found similar strain values; however, the peak SENC values in our study were slightly higher than the peak MR tagging values in our and previous published studies (16,22,23). This phenomenon can be attributed to the higher temporal resolution of SENC resulting in a higher probability of acquisition of the peak systolic contraction.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations